Several New Metrics for Evaluation of Expert Systems Based on Service-Oriented Architecture - Ali Nayebpour; Hassan Rashidi (Institute of Advanced Engineering and Science, 2013)
Modern expert systems have some limitations such as vulnerabilities, the unity of solution strategy, development problems, repair and maintenance. These limitations could be covered by Service-Oriented Architecture (SOA), due to the advantages and various applications of this architecture and its combination to expert systems. The main purpose of this paper is to survey service-oriented architecture to provide solutions for using this style in order to eliminate the short comings and optimize services in expert systems. In this paper, several metrics for evaluating expert systems based on service-oriented architecture are presented. These metrics are in six branches: agility, integrity, usability and reusability, business objectives, accessibility, offering new and applied services. For each metric some properties are presented which the expert systems show more powerful in evaluation.DOI:http://dx.doi.org/10.11591/ijece.v3i5.4032